Metal based nanoparticles trigger the differential expression of key regulatory genes which regulate iron and zinc homeostasis mechanism in finger millet. (July 2021) - Chandra, Ajay Kumar; Pandey, Dinesh; Tiwari, Apoorv; Gururani, Kavita; Agarwal, Aparna; Dhasmana, Anupam; Kumar, Anil
Abstract: Since green revolution, the food systems in most of the countries have dramatically changed but undernourishment still remains an inflammable problem. This alarming condition is even increasing due to the marginal supply of nutri-enriched food to eat. Under such chronically undernourished condition, dietary deficiencies of iron and zinc lead to compromised planetary health and economic losses. Given the micronutrient deficiency, there is an urgent call to devise or innovative a strategy for providing the requisite amount of iron and zinc in their daily intake to counter this issue. Thus being a high iron and zinc accumulating crop, finger millet can be efficiently used as an intricate model system to explore the prospects of genetic and molecular mechanisms which are responsible for nutrient enrichment in grains. We report here a promising role of nanotechnology in terms of their iron and zinc biofortification potentials in the finger millet. Comparative in vitro evaluation using lower concentration of Fe3 O4 (100 ppm) and ZnO (5 ppm) nanoparticles (NPs) display a significant promotory effect on both mineral assimilation and growth parameters whereas higher concentrations of NPs, FeSO4 .7H2 O and ZnSO4 .7H2 O bulk salts marked inhibitory effects. The molecular modelling and docking interaction analysis infers that these nano-minerals may bind to significantly influence the modulation of regulatory genes. The result was further validated using real time PCR profiling. The differential expression profiling resulted in higher transcriptional modulation of iron and zinc transporters particularly EcFER1, EcIRT2, EcYSL2, EcZIP1 and EcZTP29 in nano-primed genotypes compared to controls. Thus in conclusion, being a nutrient by default and stress-resilient crop, nanoparticle formulations in finger millet triggers the epigenetic regulation of potential key regulatory genes involved in iron and zinc homeostasis. The study also indicates innovative role of nano-seed priming for biofortification which triggers differential modulation of iron and zinc acquisition and enrichment in grains despite nutrient limiting conditions. Graphical abstract: Image 1 Highlights: Lower concentration of Fe3 O4 and ZnO Nanoparticles promote mineral assimilation. Higher concentrations of Fe and Zn NPs and bulk salts inhibit mineral acquisition. Molecular docking studies show interaction of Fe and Zn NPs with regulatory genes. Over expression of genes modulate minerals acquisition in finger millet grain. Nanoparticle formulations trigger epigenetic regulation of key regulatory genes.